An updated genus‐wide phylogenetic analysis of Arisaema (Araceae) with reference to sections. (30th June 2016) - Ohi‐Toma, Tetsuo; Wu, Sugong; Murata, Hiroko; Murata, Jin
Abstract : Arisaema has a long and complicated taxonomic history regarding its infrageneric classification. In the latest system, 14 sections were recognized, based on an unpublished, tentative phylogenetic analysis; in addition the type species and nomenclatural priority for each section were confirmed. Here, we present an updated, genus‐wide phylogenetic analysis, based on four plastid non‐coding regions (3 ′trnL – trnF, rpl20– 5 ′rps12, psbB – psbH and rpoC2 – rps2 ) for > 150 accessions. The maximum parsimony and maximum likelihood phylogenetic analyses identified eight major clades and one branch with unique sequence variation, although the relationships were unclear due to a polytomy and weak support. In the phylogenetic trees, most of the sections proposed in the latest system were distinct and corresponded to the major clades, but some sections are not monophyletic. On the basis of the phylogenetic relationship: (1) A. schimperianum is treated as a member of section Arisaema, rather than section Tenuipistillata or section Sinarisaema ; and (2) section Fimbriata, which was synonymised into section Attenuata in the latest system but is morphologically distinct from the other species, is redefined as a monotypic section. In conclusion, we recognize 15 sections of Arisaema and species‐level classifications are discussed in a phylogenetic context.